Blue Economy: Pokdarwis Assistance In Financial Management of The Puger Kulon Maritime Area Through A Social Accounting Framework Approach - Andriana Andriana; Resha Dwi Ayu Pangesti M; Husnunnida Maharani; Taufik Kurrohman; Hendrawan Santosa Putra; Ismi Khoirun Nisa (International Journal Of Community Service, 2025)
Puger Kulon Village possesses superior potential not only in processed fishery derivative products but also in the promising maritime business sector. This diversity of potential makes the village a maritime circular business with a sustainable economic concept. However, limited human resources are limited, preventing the village from mapping the development of this circular business. The Puger Kulon village community has not yet implemented structured Standard Operating Instructions (SOPs) and integrated financial planning and management. The community service program for this assisted village consists of several stages, including: 1. determining the mapping and creating SOPs for the development of the Puger Kulon Village maritime circular business sector; 2. creating and organizing social accounting-based financial reports; 3. providing education and training related to marketing the maritime business potential. The resulting outputs include the availability of Standard Operating Instructions (SOPs) and guidelines for preparing financial reports.